Adaptations of microbial communities and dissolved organics to seasonal pressures in a mesotrophic coastal Mediterranean lake. (14th February 2022) - Selak, Lorena; Osterholz, Helena; Stanković, Igor; Hanžek, Nikola; Gligora Udovič, Marija; Dittmar, Thorsten; Orlić, Sandi
Summary: In lake ecosystems, changes in eukaryotic and prokaryotic microbes and the concentration and availability of dissolved organic matter (DOM) produced within or supplied to the system by allochthonous sources are components that characterize complex processes in the microbial loop. We address seasonal changes of microbial communities and DOM in the largest Croatian lake, Vrana. This shallow lake is connected to the Adriatic Sea and is impacted by agricultural activity. Microbial community and DOM structure were driven by several environmental stressors, including drought, seawater intrusion and heavy precipitation events. Bacterial composition of different lifestyles (free‐living and particle‐associated) differed and only a part of the particle‐associated bacteria correlated with microbial eukaryotes. Oscillations of cyanobacterial relative abundance along with chlorophyll a revealed a high primary production season characterized by increased levels of autochthonous DOM that promoted bacterial processes of organic matter degradation. From our results, we infer that in coastal freshwater lakes dependent on precipitation‐evaporation balance, prolonged dry season coupled with heavy irrigation impact microbial communities at different trophic levels even if salinity increases only slightly and allochthonous DOM inputs decrease. These pressures, if applied more frequently or at higher concentrations, could have the potential to overturn the trophic state of the lake.